Reservoir-induced changes to fluvial fluxes and their downstream impacts on sedimentary processes: The Changjiang (Yangtze) River, China. (10th November 2018) - Gao, Jian Hua; Jia, Jianjun; Kettner, Albert J.; Xing, Fei; Wang, Ya Ping; Li, Jun; Bai, Fenglong; Zou, Xinqing; Gao, Shu
Abstract: Reservoir interception has significantly affected the fluvial sediment budget as well as the sedimentary processes of the entire Changjiang catchment. To evaluate the impact of reservoirs, we analyze the combined effects of 1037 large and medium-sized reservoirs on the fluvial flux in general, and more specifically on the sedimentary processes in the middle and lower reaches. Results indicate that reservoir emplacement in the Changjiang catchment currently reduces the sediment load towards the East China Sea by 453 Mt y −1 . Estimates at Yichang station show that the sediment discharge would exceed 555 Mt y −1, if there were no reservoirs involved. It is expected that in the near future, more dams will be constructed. The entire reach of the Changjiang River can be divided at Yichang station into two distinctly characterised reaches with regard to sedimentation, where the upper reach exhibits mostly siltation (over 589 Mt y −1 of sediment deposition), and the lower reach is affected by erosion (sediment loss, including sand extraction, exceeding 112 Mt y −1 ). As a consequence, the sediment flux to the sea will further decrease to 100 Mt y −1 . Due to human interference, the upstream sediment load reduced and caused significant changes in the erosion/deposition pattern of the middle and lower reaches, which together altered the terrestrial sediment input to the sea. Before 2003, the upstream reaches were the dominant sediment source. After 2003, the sediment contribution of the middle and lower reaches became more important, and its sediment contribution will further increase to 78% of the total sediment load reaching the sea, after completion of the cascade reservoirs at the Jinsha Tributary. Hence, the middle and lower reaches are converting from a sediment sink to a major sediment source.